Design and Study for the Algorithm of Multimedia Messaging Service (MMS) Framework in Message Delivery - Setyono, Andik; Md Jahangir, Alam; Raed Ali, Al Saqour (2009)
The growth of Information and Communication Technology (ICT), including mobile technology, such as hand phone, PDA, notebook etc., is becoming faster day by day. Those technologies have already become an essential part of our every day life. These technologies are supported by many low-cost facilities, such as calling capabilities, SMS, MMS, playing games, browsing internet, etc. These low-cost technologies can be used to develop a mobile application. Many applications have already been developed using these facilities. This paper analyzes the behaviour of the algorithms of the MMS framework in message delivery and it also simulates an application which is developed to study the algorithms and the methods for sending and receiving MMS. The simulation results can be installed on a mobile phone, then it can send MMS to another mobile phone number and also to email server. The outcome of the proposed research indicates a potential development of mobile and internet application using MMS framework.